2004
DOI: 10.1080/00071660410001730860
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial function in turkey skeletal muscle—impact on meat quality

Abstract: 1. M. iliotibialis (MIT) and M. pectoralis (MP) of the BUT Big 6 and Kelly BBB turkey were characterised with respect to physical properties, mitochondrial function, metabolic state, morphology and meat quality. 2. Mitochondrial enzyme activity and respiration rates in MP declined with increasing age while glycolytic enzyme activity remained nearly constant. 3. There were no major differences between BUT Big 6 and Kelly BBB with respect to histological, histochemical or biochemical variables. In spite of the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Using the skinned fibre technique, Opalka et al (2004) also showed significantly higher MRAs in the MIL in comparison with the MPS, and this difference is related to the higher percentage of oxidative FTO and STO fibres in the leg muscle and the accompanied increasing oxidative metabolism, as already discussed in the previous chapter.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Using the skinned fibre technique, Opalka et al (2004) also showed significantly higher MRAs in the MIL in comparison with the MPS, and this difference is related to the higher percentage of oxidative FTO and STO fibres in the leg muscle and the accompanied increasing oxidative metabolism, as already discussed in the previous chapter.…”
Section: Discussionsupporting
confidence: 57%
“…Determination of the MRA is a method to investigate oxygen consumption of the tissue and has been analysed in muscle/meat samples from poultry (Tang et al, 2002;Opalka et al, 2004;Bottje and Carstens, 2009). Using the skinned fibre technique, Opalka et al (2004) also showed significantly higher MRAs in the MIL in comparison with the MPS, and this difference is related to the higher percentage of oxidative FTO and STO fibres in the leg muscle and the accompanied increasing oxidative metabolism, as already discussed in the previous chapter.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Investigation in broiler and turkey meat also showed no impact of a lower pH 20 min p.m. on the Pyr/ Mal-MRA results (Opalka et al, 2004;Werner et al, 2011). In all these studies, MRA was analysed with permeabilised muscle fibres.…”
mentioning
confidence: 93%